The Influence of the Contextual Teaching and Learning Model on Science Learning Outcomes of Grade V Students of SDN 06 Kelapa Tujuh - Agustin, Fadila Kharismanda; Rohmani, Rohmani; Saikia, Manjusha Deka (Ruang Publikasi Ilmiah, 2025)
Students' ability to understand science material greatly influences learning outcomes. In fact, there are still many students who have low science learning outcomes. Teacher assessment can be considered as an evaluation process that aims to collect data and indicate the level of student ability to achieve learning goals. The problem in this research is whether there is an influence of the application of the contextual teaching and learning model on the science learning outcomes of class V students at SD Negeri 06 Kelapa Tujuh for the 2024/2025 academic year. The aim of this research is to determine the effect of implementing the CTL learning model on the science learning outcomes of class V students at SD Negeri 06 Kelapa Tujuh in the 2024/2025 academic year. The research method used in this research is an experimental method with a quasi-experimental design type. The research instruments used were tests in the form of multiple choice questions, pre-research questions, pre-research questions and post-research tests. Hypothesis test results tcount = 3.905, at a significance level (α) = 0.05, we get ttable 1.677. These results show that tcount > ttable, meaning that H0 is rejected or in other words Ha is accepted. This means that there is an influence of the application of the CTL learning model on the science learning outcomes of class V students at State Elementary School 06 Kelapa Tujuh in the 2024/2025 academic year.